To solve the equation
\[ -2(-3x + 1) = -(-6x + 3), \]
we'll start by simplifying both sides.
-
Distributing on the left side: \[ -2(-3x + 1) = -2 \cdot -3x + -2 \cdot 1 = 6x - 2. \]
-
Distributing on the right side: \[ -(-6x + 3) = 6x - 3. \]
Now we can rewrite the equation with the simplified expressions:
\[ 6x - 2 = 6x - 3. \]
- Subtract \(6x\) from both sides: \[ 6x - 2 - 6x = 6x - 3 - 6x \implies -2 = -3. \]
This statement \(-2 = -3\) is false, which means there are no solutions to the equation.
Therefore, the answer is:
\[ \text{No solution.} \]